Posterior Capsular Plication Constrains the Glenohumeral Joint by Drawing the Humeral Head Closer to the Glenoid and Resisting Abduction. Issue 8 (18th August 2015) - DeAngelis, Joseph P.; Hertz, Benjamin; Wexler, Michael T.; Patel, Nehal; Walley, Kempland C.; Harlow, Ethan R.; Manoukian, Ohan S.; Masoudi, Aidin; Vaziri, Ashkan; Ramappa, Arun J.; Nazarian, Ara
Background: Shoulder pain is a common problem, with 30% to 50% of the American population affected annually. While the majority of these shoulder problems improve, there is a high rate of recurrence, as 54% of patients experience persistent symptoms 3 years after onset. Purpose: Posterior shoulder tightness has been shown to alter glenohumeral (GH) kinematics. Clinically, posterior shoulder contractures result in a significant loss of internal rotation and abduction (ABD). In this study, the effect of a posterior capsular contracture on GH kinematics was investigated using an intact cadaveric shoulder without violating the joint capsule or the rotator cuff. Study Design: Controlled laboratory study. Methods: Glenohumeral motion, humeral load, and subacromial contact pressure were measured in 6 fresh-frozen left shoulders during passive ABD from 60° to 100° using an automated robotic upper extremity testing system. Baseline values were compared with the experimental condition in which the full thickness of posterior tissues was plicated without decompressing the joint capsule. Results: Posterior soft tissue plication resulted in increased compression between the humeral head and the glenoid (axial load) at 90° of ABD. Throughout ABD, the posterior contracture increased the anterior and superior moment on the humeral head, but it did not change the GH kinematics in this intact model. As a result, there was no increase in the subacromial contact pressure during ABD with posterior plication. Conclusion: In an intact cadaveric shoulder, posterior contracture does not alter GH motion or subacromial contact pressure during passive ABD. By tightening the soft tissue envelope posteriorly, there is an increase in compressive load on the articular cartilage and anterior/superior force on the humeral head. These findings suggest that subacromial impingement in the setting of a posterior soft tissue contracture may result from alterations in scapulothoracic motion, not changes in GH kinematics. Clinical Relevance: This investigation demonstrates that posterior capsular plication increases the axial load on the shoulder joint during ABD. While a significant difference from baseline was observed in the plicated condition, posterior capsular plication did not change GH motion or subacromial contact pressure significantly.